Case study on delay factors in steel bridge construction - Hazim Adly Harun, Harun (2015)
Delay in construction is a norm in certain instances especially in large complex construction projects. With different kinds of delay causing different length of delays to the completion date of the project make it a real deal that needs attention by the authorities and the construction parties. Delay factors come in many forms that impact the project differently. In view of the Industrialized Building System (IBS) approach that aims to provide a better quality construction, solutions to the delay factors have to be relevant in both traditional and modern system. This research aims to find out the factors that are directly associated to IBS structures particularly steel bridge through observations and interview sessions with the technical workers involved. Structured interview questions are used in seeking for information. This is then followed by analysis made using the observations made at the factory and site.Discussions and rankings of associated delay factors are done to highlight the best solutions.